Leishmaniose visceral canina: estudo histológico e imuno-histoquímico renal com ênfase na fibropoese - Adriano Francisco Alves (2018)
Extracellular matrix (ECM) changes studies, in visceral leishmaniasis, are mainly those related to collagen deposition (fibropoese). There are studies in canine visceral leishmaniasis (LVC) showing intense fibropoiesis associated to a chronic inflammation that occurs in various organs such as lungs (interstitial pneumonitis), spleen (granulomatous sclerosing splenitis), liver (granulomatous hepatitis), lymph nodes (granulomatous lymphadenitis) and kidneys (glomerulonephritis and interstitial nephritis). However, according to the literature, there are no renal fibropoiesis detailed studies, either glomerular or tubulointerstitial renal lesions in dogs naturally or experimentally infected with parasites of the genus Leishmania, L. (L.) infantum specie. Furthermore, there is no detailed description of the pathological aspects of the kidneys of dogs experimentally infected with L. (L.) infantum. In Brazil, the main etiological agent of the LVC is the species L. (L.) infantum, but recent works have increasingly demonstrated the participation of another viscerotropic species: L. (L.) amazonensis. The objectives of this work were to study some pathological aspects of kidneys obtained from dogs naturally infected with L. infantum and from dogs experimentally infected with two different strains of L. infantum and a single strain of L. amazonensis, with special emphasis on fibrotic process. Eighty-seven specimens of paraffin-embedded kidney fragments were collected as follows: (1) sixty-two kidney samples of adult mongrel dogs, naturally infected with L. infantum, with positive serological and parasitological diagnosis, obtained from Centers of Zoonoses of the metropolitan region of the municipality Belo Horizonte, MG, denominated group CNI; (2) five kidney samples of adult Beagles experimentally infected with L. infantum strain MCAN / BR / 2002 / BH401 at the dose of 5x107 promastigotes/ml of L. infantum, endovenous route, denominated group BH401; (3) eleven kidney samples of adult Beagles dogs experimentally infected with L. infantum strain MCAN / BR / 2000 / BH400, at the same dose and same route of the previous group, denominated group BH400. (4) five kidney samples of adult Beagles experimentally co-inoculated with L. infantum strain MCAN / BR / 2002 / BH401 (BH401) and L. amazonensis strain PH8 (FLA / BR / 1967 / PH8), denominated Co-inoculated group. The dogs of this group were infected with promastigote forms of L. infantum at the dose of 2.5 x 107 parasites / ml and promastigotes forms of L. amazonensis at the dose of 2.5 x 107 parasites / ml, both intravenously, in a single strain. The experimental infection occurred at 11 months of life of each animal for all groups, and the time interval of the experimental infection was two years for the BH401 and co-infected groups, and eighteen months for the BH400 group. All animals with Leishmania-positive parasitological examinations at 6-8 months post-infection and remained positive until the end of the experimental trial; (5) four kidney samples from adult Beagle dogs, two and a half years old, all with negative serological and parasitological tests for Leishmania, denominated control group (CC). . The euthanasia of these animals occurred along with those of the BH401 and Co-inoculated groups. After histological analysis by conventional optical microscopy, all animals revealed glomerular and interstitial fibropoiesis, discrete to intense, associated with different types of glomerulonephritis and chronic interstitial nephritis. However, the frequency of lesions was different between groups. Fibrosis, for example, was markedly more intense in the BH401 group, followed by animals in the CNI group. Immunohistochemical study to investigate some aspects of the mechanisms of this fibrosis was carried out targeting cell markers for myofibroblasts (mesenchymal markers) such as alpha-actin (áSMA) and vimentin. The cytokine transforming growth factor beta (TGF-â) and metalloproteinases (MMPs), cellular enzymes secreted inactivated related to ECM remodeling, type 2 (MMP-2), 7 (MMP-7) and 9 (MMP9), were also investigated. Again, the BH401 group, followed by the Co-inoculated group, was the most striking for the visualization of the expression of all these markers when compared to the other groups. Membranoproliferative glomerulonephritis was more frequent in the BH401 (75%) and CNI (75%) groups. Membranous glomerulonephritis (by means of a differential diagnosis of Jones silver metenamine) occurred in all animals of the Co-inoculated group and in some animals of the BH400 group (33.3%). Sclerosing glomerulonephritis appeared only in animals of group BH401 (100%). Morphometrical study of glomerular cellularity and mesangial matrix deposition visualized by the special staining as periodic acid shiff (PAS) and Masson triochrome confirmed more striking lesions in the BH401 group. Mesangial macrophages, L1 and CD163 positive cells, were visualized by confocal microscopy preferably in the BH401 group reinforcing the described findings. The presence of intracellular amastigotes forms of Leishmania, visualized by immunohistochemistry, was observed especially in the BH401 group, followed by the CNI group, but not visualized in the BH400 group and in the CC dogs. The results confirm renal fibrosis with intense labeling for á-SMA, vimentin and TGF-beta, and MMPs, especially the BH401 group, indicating that the MCAN / BR / 2002 / BH401 strain is a good choice for the study of renal LVC experimental model.